Robot móvil interactivo de apoyo al aprendizaje del alfabeto en niños de primer año de educación básica. - Párraga Llorente , Rafael Wladimir (2024)
Teaching the alphabet to first-year basic education students presents significant challenges related to motivation and concept retention. This project aims to examine the use of an interactive mobile robot to support alphabet learning, providing a more dynamic alternative to traditional methods in the context of a developing country. The methodology involved a systematic review to identify design guidelines, followed by the construction of the robot and a user study conducted with students and teachers. The results showed that the use of the robot positively contributes to student motivation, promoting more active participation and improved retention of fundamental alphabet concepts. Furthermore, the robot’s ease of use and playful design were key factors in its acceptance by both teachers and students. In conclusion, integrating interactive mobile robots into early education holds promise for enhancing the teaching process, fostering greater motivation, and achieving meaningful learning in resource-constrained contexts. These findings suggest that educational robotics has significant potential to improve learning experiences in developing countries.